Molecular Cloning and Functional Analysis of Three Type D Endogenous Retroviruses of Sheep Reveal a Different Cell Tropism from That of the Highly Related Exogenous Jaagsiekte Sheep Retrovirus - Palmarini, Massimo (American Society for Microbiology, 2000)
Integrated into the sheep genome are 15 to 20 copies of type D endogenous loci that are highly related to two exogenous oncogenic viruses, jaagsiekte sheep retrovirus (JSRV) and enzootic nasal tumor virus (ENTV). The exogenous viruses cause infectious neoplasms of the respiratory tract in small ruminants. In this study, we molecularly cloned three intact type D endogenous retroviruses of sheep (enJS56A1, enJS5F16, and enJS59A1; collectively called enJRSVs) and analyzed their genomic structures, their phylogenies with respect to their exogenous counterparts, their capacity to form viral particles, and the expression specificities of their long terminal repeats (LTRs). In addition, the pattern of expression of enJSRVs in vivo was studied by in situ hybridization. All of the three enJSRV proviruses had open reading frames for at least one of the structural genes. In particular, enJS56A1 had open reading frames for all structural genes, but it could not assemble viral particles when highly expressed in human 293T cells. We localized the defect for viral assembly in the first two-thirds of the gag gene by making a series of chimeras between enJS56A1 and the exogenous infectious molecular clone JSRV(21). Phylogenetic analysis distinguished five ovine type D retroviruses: enJSRV groups A and B, ENTV, and two exogenous JSRV groups (African versus United Kingdom/North America isolates). Transient transfection assays indicated that the LTRs of the three enJSRVs were not preferentially active in differentiated lung epithelial cells. This suggests that the pulmonary tropic JSRV developed from a type D retrovirus that did not have lung specificity. Consistent with this, in situ hybridization of a panel of normal ovine tissues revealed high expression of enJSRV mRNA in the luminal epithelium and glandular epithelium of the uterus; lower expression was localized in the lamina propria of the gut and in the bronchiolar epithelium of the lungs.